Partnering With Patients to Bridge Gaps in Consent for Acute Care Research - Dickert, Neal W.; Bernard, Amanda Michelle; Brabson, JoAnne M.; Hunter, Rodney J.; McLemore, Regina; Mitchell, Andrea R.; Palmer, Stephen; Reed, Barbara; Riedford, Michele; Simpson, Raymond T.; Speight, Candace D.; Steadman, Tracie; et al. (American journal of bioethics, 2020)
Clinical trials for acute conditions such as myocardial infarction and stroke pose challenges related to informed consent due to time limitations, stress, and severe illness. Consent processes should be sensitive to the context in which trials are conducted and to needs of patients and surrogate decision-makers. This manuscript describes a collaborative effort between ethicists, researchers, patients, and surrogates to develop patient-driven, patient-centered approaches to consent for clinical trials in acute myocardial infarction and stroke. Our group identified important ways in which existing consent processes and forms for clinical trials fail to meet patients' and surrogates' needs in the acute context. We collaborated to create model forms and consent processes that are substantially shorter and, hopefully, better-matched to patients' and surrogates' needs and expectations from the perspective of content, structure, and tone. These changes, however, challenge some common conventions regarding consent.